Significant Role of Collagen XVII And Integrin β4 in Migration and Invasion of The Less Aggressive Squamous Cell Carcinoma Cells - Moilanen JM; Loffek S; Kokkonen N; Salo S; Vayrynen JP; Hurskainen T; Manninen A; Riihila P; Heljasvaara R; Franzke CW; Kahari VM; Salo T; et al. (NATURE PUBLISHING GROUP, 2022)
Collagen XVII and integrin alpha 6 beta 4 have well-established roles as epithelial adhesion molecules. Their binding partner laminin 332 as well as integrin alpha 6 beta 4 are largely recognized to promote invasion and metastasis in various cancers, and collagen XVII is essential for the survival of colon and lung cancer stem cells. We have studied the expression of laminin.2, collagen XVII and integrin beta 4 in tissue microarray samples of squamous cell carcinoma (SCC) and its precursors, actinic keratosis and Bowen's disease. The expression of laminin.2 was highest in SCC samples, whereas the expression of collagen XVII and integrin beta 4 varied greatly in SCC and its precursors. Collagen XVII and integrin beta 4 were also expressed in SCC cell lines. Virus-mediated RNAi knockdown of collagen XVII and integrin beta 4 reduced the migration of less aggressive SCC-25 cells in horizontal scratch wound healing assay. Additionally, in a 3D organotypic myoma invasion assay the loss of collagen XVII or integrin beta 4 suppressed equally the migration and invasion of SCC-25 cells whereas there was no effect on the most aggressive HSC-3 cells. Variable expression patterns and results in migration and invasion assays suggest that collagen XVII and integrin beta 4 contribute to SCC tumorigenesis.